Effect of storage temperature on cultured epidermal cell sheets stored in xenobiotic-free medium. - Catherine Jackson (Public Library of Science (PLoS), 2014)
Cultured epidermal cell sheets (CECS) are used in regenerative medicine in patients with burns, and have potential to treat limbal stem cell deficiency (LSCD), as demonstrated in animal models. Despite widespread use, short-term storage options for CECS are limited. Advantages of storage include: flexibility in scheduling surgery, reserve sheets for repeat operations, more opportunity for quality control, and improved transportation to allow wider distribution. Studies on storage of CECS have thus far focused on cryopreservation, whereas refrigeration is a convenient method commonly used for whole skin graft storage in burns clinics. It has been shown that preservation of viable cells using these methods is variable. This study evaluated the effect of different temperatures spanning 4°C to 37°C, on the cell viability, morphology, proliferation and metabolic status of CECS stored over a two week period in a xenobiotic-free system. Compared to non-stored control, best cell viability was obtained at 24°C (95.2±9.9%); reduced cell viability, at approximately 60%, was demonstrated at several of the temperatures (12°C, 28°C, 32°C and 37°C). Metabolic activity was significantly higher between 24°C and 37°C, where glucose, lactate, lactate/glucose ratios, and oxygen tension indicated increased activation of the glycolytic pathway under aerobic conditions. Preservation of morphology as shown by phase contrast and scanning electron micrographs was best at 12°C and 16°C. PCNA immunocytochemistry indicated that only 12°C and 20°C allowed maintenance of proliferative function at a similar level to non-stored control. In conclusion, results indicate that 12°C and 24°C merit further investigation as the prospective optimum temperature for short-term storage of cultured epidermal cell sheets.